2013
DOI: 10.1186/2193-1801-2-384
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen doping of HTSC and resistive switching in HTSC-based heterostructures

Abstract: The studies of the bipolar resistive switching effect in thin film heterojunctions (YBa2Cu3O7−δ/Ag) and (Nd 2−xCexCuO4−y/Ag) have exhibited the role of oxygen as a doping element in hole- and electron-doped HTSC compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…NCCO is also the representative of electrondoped high-temperature superconductors. In [43,44,45] detailed investigations of BERS in various epitaxial NCCO-based structures were carried out. They found that c-oriented epitaxial NCCO films represent a structure with few tens nm thick phase of oxygen-deficient Nd0.5Ce0.5O1.75 (NCO) oxide intergrown on the surface.…”
Section: Nd186ce014cuo4mentioning
confidence: 99%
“…NCCO is also the representative of electrondoped high-temperature superconductors. In [43,44,45] detailed investigations of BERS in various epitaxial NCCO-based structures were carried out. They found that c-oriented epitaxial NCCO films represent a structure with few tens nm thick phase of oxygen-deficient Nd0.5Ce0.5O1.75 (NCO) oxide intergrown on the surface.…”
Section: Nd186ce014cuo4mentioning
confidence: 99%